Deradikalisasi Pendidikan Islam Berbasis Khazanah Pesantren - Masduqi, Irwan (Jurnal Pendidikan Islam, 2013)
Violence in the name of religion often happens in Indonesia. Pesantren is considered as a nest of terrorism because it has been being tought religious radicalism here. This study can be concluded that Islam is as a religion of universal love (rahmatan lil ‘alamin). Here, it is tought education that upholds the principle of mutual respect for differences, harmony, peace, civility, and other manifestations of noble character. But the teachings of “rahmatan lil ‘alamin” is often reduced to justify violence in the name of religion by sensible dogmatic radical groups. De-radicalizational steps are needed to develop Islamic education that is more humane.